Рост Eudiaptomus graciloides (Lill.) при разных условиях питания - Крючкова, Н.М.; Рыбак, В.X. (Гидробиологический журнал, 1974)
В экспериментах на Е. graciloides определены в зависимости от возраста животных и концентрации корма рационы, траты на обмен и рассчитаны коэффициент использования на рост усвоенного корма и его усвояемость. The long-term experiments with feeding and growth of E. graciloides were carried out with the use of Chlamydomonas eugametos and Chlorella vulgaris as hosts. Allowances and metabolic expenditures were determined with reference to the food concentration and animal’s age. The coefficients of the assimilated food use for the growth and food digestability are calculated.